“To Assess the Various Methods Practiced to Study and Hurdles Faced by Nursing Students of Selected Colleges in Mumbai.” - Mrs. Shilpa Ashok Shettigar; Ms. Priyanka Gomale; Ms. Kajal Sharma (Revista Electronica de Veterinaria, 1970)
Background:Education is an investment to development and poor study methods should not compromise the mandate of higher education institutions to generate, preserve and disseminate knowledge and produce high quality graduates. Universities admit students with varying backgrounds in terms of learning/study styles, levels of preparedness and concepts of university education. Some were "drilled", spoon fed, taught for exams, or have wrong purposes/values of university learning.  Aim and Objectives: This study aimed to assess the various methods practiced to study and hurdles faced by nursing students of selected colleges in Mumbai. To assess various methods practiced to study by nursing students. To assess hurdles faced to study by nursing students. Materials and Methods A descriptive evaluation approach with group of students, survey design was used. Total 100 samples were selected to assess the various methods practiced to study and different types of hurdles faced while studying. Data collection involved a structured, semi structured questionnaire and attitude scale was used as a tool to collect data with self-reported technique. Statistical analysis included descriptive statistics and paired t-test. Results: practiced to study, where the mean of always is 50.1, mean of often is 28.6, mean of sometimes is 18.1, mean of sudden is 1.7, mean of never is 1.2. Whereas the overall mean of the attitude test to assessing the hurdles faced to study. Where the mean of always is 18, mean of often is 23.3, mean of sometimes is 39.5, mean of sudden is 9.6, mean of never is 9.5.  Conclusion: The result of the study and extent of this impact depend on several factors such as attitude of students and practices followed by them to cope up with hurdles while study, unable to focus on topic, low motivations, too many distractions, struggling with time management, struggling with financial problems, the overall mean of the attitude test to assessing the various methods practiced to study